Future Gold Commodity: Indonesian Ulema Council Vs Lajnah Daimah lil Buhuts al-’Ilmiyyah wal Ifta - Ayu Rahayu Nurhalizah; Ach Fageh (JURIS (Jurnal Ilmiah Syariah), 2022)
Technological developments have made it easier to buy gold. Buying gold in installments or online is currently a trend and growing in Indonesia. Buying and selling transactions like this have not been explained in detail in classical fiqh. This research is a normative research with a comparative approach, namely comparing the laws of a country with the laws of one or more other countries regarding the same case. The data analysis techniques used in this article are in the form of data reduction, data presentation, and drawing conclusions. The results of this study state that there are differences of opinion between the Indonesian Ulema Council and the Saudi Arabian Fatwa Institute. The Saudi Arabian fatwa institution issued a fatwa regarding the prohibition of buying and selling gold in futures, because gold is a type of usury property and contains 'illat as a unit of price or means of payment. Meanwhile, the National Sharia Council of the Indonesian Ulema Council stipulates a fatwa regarding the permissibility of buying and selling gold in cash or futures, because at this time, gold is no longer a price (tsaman), but gold is an ordinary merchandise or commodity. The discussion about buying and selling gold is in the realm of ijtihad, which is inseparable from differences of opinion (khilafiyah), because there is no definite text in this matter.